Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 16320 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "TaxonKey is Tardigrada" ] } The dataset includes 16320 records from 125 constituent datasets: 10 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 1 records from Données naturalistes faune du Conservatoire des espaces naturels Auvergne saisies avant le 18 février 2019.. 2 records from (Table 4) Meiofauna abundance in surface sediments of Cape Fear. 4 records from (Table 3) Meiofauna abundance in surface sediments of Cape Lookout. 1 records from Summary on benthic studies of the Southern Bight of the North Sea and its adjacent continental estuaries (Western Scheldt and Eems-Dollard) between 1976 and 1978. 9 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 302 records from Geographically tagged INSDC sequences. 1 records from Artenvielfalt der Nordsee - Sylt. 3 records from UAM Insect Collection (Arctos). 2 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 6 records from South Australian Museum Australia provider for OZCAM. 11359 records from Tardígrados del Centro de Colecciones Biológicas de la Universidad del Magdalena CBUMAG. 1 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 8 records from Western Australian Museum provider for OZCAM. 1 records from Nivå Bay species list, Zealand, Denmark. 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 9 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 1 records from Centre for Biodiversity Genomics - Canadian Specimens. 2 records from National Trust Species Records. 65 records from Wetland Invertebrate and Environmental Data 2010 Sampling Events. 1 records from Integrative description of Macrobiotus canaricus sp. nov. with notes on M. recens (Eutardigrada: Macrobiotidae). 1 records from Arctic Ocean Diversity. 1 records from Doryphoribius chetumalensis sp. nov. (Eutardigrada: Isohypsibiidae) a new tardigrade species discovered in an unusual habitat of urban areas of Mexico. 7 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 10 records from Pollen record from Mamontovy Klyk. 1 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 1 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 2 records from Macrobiotus nebrodensis and Adropion vexatum, two new species of Eutardigrada (Tardigrada, Parachela) from Sicily. 1 records from Fife Nature Records Centre combined dataset. 613 records from Invertebrates Collection of the Swedish Museum of Natural History. 3 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/395-1. 1 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 12 records from Sustainable Rivers Audit. 1 records from Annotated zoogeography of non-marine Tardigrada. Part II: South America. 204 records from Australian Museum provider for OZCAM. 1 records from Welsh Invertebrate Database (WID). 1 records from A new tardigrade species of the genus Neostygarctus Grimaldi de Zio et al., 1982 (Tardigrada, Arthrotardigrada) from the Great Meteor Seamount, Northeast Atlantic. 171 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 1 records from Marine Biological Sample Database, JAMSTEC. 37 records from Paleobiology Database. 9 records from Observation.org, Nature data from around the World. 14 records from IndOBIS, Indian Ocean Node of OBIS. 309 records from Canadian Museum of Nature General Invertebrate Collection. 2 records from Two new species of Eutardigrada from Victoria Land, Antarctica. 2 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 1 records from Invertebrate Site Register - England (1738-2005).. 23 records from Museum of Comparative Zoology, Harvard University. 3 records from Macrobenthos and Meiobenthos Tuktoyaktuk Harbor and Mason Bay 1985-1988 NOGAP. 3 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 3 records from Batillipes (Tardigrada, Arthrotardigrada) from the Portuguese coast with the description of two new species and a new dichotomous key for all species. 2 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 56 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 1 records from Meiobenthic assemblages colonizing artificial soft sediments at 20 m depth in Arctic glacial Kongsfjorden, Spitsbergen, Svalbard - individual number. 25 records from Vertical distribution of meiofauna in the North Sea and the Westerschelde estuary in 1993 and 1994. 2 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 12 records from CAS Invertebrate Zoology (IZ). 4 records from Bibliographique de la faune, la flore et la fonge de France métropolitaine et outre-mer. 5 records from Benthic meiofauna abundance in surface sediment during cruise CD86. 296 records from Invertebrates compiled by W.Block. 1 records from Comparative study of the meiobenthos in the Arctic region in 1991. 3 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 9 records from naturgucker. 5 records from NaGISA Project. 38 records from Collection Tardigrada SMF. 15 records from Tardigrad collection of the National Museum of Nature and Science. 23 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 3 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 1 records from BB-Biodiversität b. 3 records from iNaturalist Research-grade Observations. 12 records from Current knowledge on Mexican tardigrades with a description of Milnesium cassandrae sp. nov. (Eutardigrada: Milnesiidae) and discussion on the taxonomic value of dorsal pseudoplates in the genus Milnesium Doyère, 1840. 3 records from Revisiting Calohypsibiidae and Microhypsibiidae: Fractonotus Pilato, 1998 and its phylogenetic position within Isohypsibiidae (Eutardigrada: Parachela). 5 records from RNF - Données de la Fédération des Réserves Catalanes. 53 records from MDFRC macroinvertebrate survey. 47 records from Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Colección de Paleovertebrados. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 1 records from Bryochoerus liupanensis sp. nov. and Pseudechiniscus chengi. sp. nov. (Tardigrada: Heterotardigrada: Echiniscidae) from China. 1 records from A description of Macrobiotus horningi sp. nov. and redescriptions of M. maculatus comb. nov. Iharos, 1973 and M. rawsoni Horning et al., 1978 (Tardigrada: Eutardigrada: Macrobiotidae: hufelandi group). 11 records from Meiobenthic community in the Westerschelde estuary between 1977 and 1979. 3 records from Caracterización de organismos asociados a microplásticos en las playas de Santa Marta. 4 records from Type Localities for organisms and fossils first described from Antarctica. 2 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 5 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 3 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 2 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE2. 1453 records from Invertebrates excl. Entomology at the Natural History Museum of Denmark. 130 records from NMNH Extant Specimen Records. 8 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 25 records from Artportalen (Swedish Species Observation System). 21 records from Norwegian Species Observation Service. 24 records from Meiobenthos of target sites of Crimea in 2009/2010. 1 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 3 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 3 records from Revision of Angursa (Arthrotardigrada: Styraconyxidae) with the description of a new species from Japan. 6 records from Integrative taxonomy identifies two new tardigrade species (Eutardigrada: Macrobiotidae) from Greenland. 2 records from ALA species sightings and OzAtlas. 309 records from Annotated zoogeography of non-marine Tardigrada. Part IV: Africa. 1 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 1 records from Distribution of meiobenthos in sediment core M19_239-2 of the northeastern Atlantic (Table 1). 19 records from Jeux de données provenant de l'ATBI Mercantour. 2 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 18 records from BioFokus. 3 records from Marine invertebrate collection NTNU University Museum. 2 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 1 records from Enrichment of organohalide respiring bacteria. 1 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE6. 11 records from NW pacific deep-sea benthos distribution and abundance (Beneficial Project). 5 records from Queensland Museum provider for OZCAM. 5 records from Recent Invertebrates Specimens. 4 records from Invertebrate Zoology Division, Yale Peabody Museum. 3 records from Three new Batillipes species (Arthrotardigrada: Batillipedidae) from the Brazilian coast. 7 records from Integrative redescription of Hypsibius pallidoides Pilato et al., 2011 (Eutardigrada: Hypsibioidea) with the erection of a new genus and discussion on the phylogeny of Hypsibiidae. 317 records from International Barcode of Life project (iBOL). 1 records from BRERC species records from all years at full resolution excluding Notable Species within the last 10 years. 1 records from Integrative taxonomy identifies Macrobiotus papei, a new tardigrade species of the Macrobiotus hufelandi complex (Eutardigrada: Macrobiotidae) from the Udzungwa Mountains National Park (Tanzania). 4 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 3 records from Two new species of the Macrobiotus hufelandi complex (Tardigrada: Eutardigrada: Macrobiotidae) from Australia and India, with notes on their phylogenetic position. 3 records from (Fig. 3) Pollen counts of the PG1756 core from Lake Billyakh. 20 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 7 records from Bioblitz 2013 Copenhagen Denmark. 3 records from 1778-1998 Ivor Rees North Wales Marine Fauna Ad-hoc sightings shore and ship-based surveys. 1 records from Diveboard - Scuba diving citizen science observations. 1 records from A new species of Diphascon (Tardigrada: Hypsibiidae) from Northern China supported by integrated taxonomy. 2 records from An integrative redescription of Hypsibius dujardini (Doyère, 1840), the nominal taxon for Hypsibioidea (Tardigrada: Eutardigrada). 2 records from KU Museum of Invertebrate Paleontology. 1 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences